The NATO Members and the Budget Guidelines in the Final Year: 2024 - Matthijs, Herman (Advances in Social Sciences Research Journal, 2024)
This study examines the defence expenditures of the NATO (North Atlantic Treaty Organisation) member countries over the period 2014-2024 and this in relation to the NATO 2014 summit decision of Wales. The research of this article is to examine the following points: How has defence spending by the member states evolved in the period under consideration (2014 – 2024) and more specifically the evolution to the 2% GDP (Grand Domestic Product) military expenditures; Which states already meet the second target of the 2014 Wales summit, namely: the 20% investment in equipment of the national military budget. The current figures are based on the primary budgetary sources as published by the NATO, namely: the defence expenditures of NATO countries (2014-2024). (see references).